Neurophysiological Correlates of Visual Dominance: A Lateralized Readiness Potential Investigation - Li, You; Liu, Mingxin; Zhang, Wei; Huang, Sai; Zhang, Bao; Liu, Xingzhou; Chen, Qi (Frontiers in Psychology, 2017)
When multisensory information concurrently arrives at our receptors, visual information often receives preferential processing and eventually dominates awareness and behavior. Previous research suggested that the visual dominance effect implicated the prioritizing of visual information into the motor system. In order to further reveal the underpinning neurophysiological mechanism of how visual information is prioritized into the motor system when vision dominates audition, the present study examined the time course of a particular motor activation ERP component, the lateralized readiness potential (LRP), during multisensory competition. The onsets of both stimulus-locked LRP (S-LRP) and response-locked LRP (R-LRP) were measured. Results showed that, the R-LRP onset to the auditory target was delayed about 91 ms when it was paired with a simultaneous presented visual target, compared to that when it was presented by itself. For the visual target, however, the R-LRP onset was comparable irrespective of whether it was paired with an auditory target or not. No significant difference were obtained for the onsets of S-LRP. Taken together, the time courses of LRPs consistently indicated that visual information was preferentially processed within the motor system, which coincides with the previous finding that the dorsal visual stream prioritizes the flow of visual information into the motor system.